Molecular characterisation of DDX49 - Kapllanaj, Fiorela (2024)
DEAD box proteins are the largest family of RNA helicases, composed of 37 members and are involved in the central and essential physiological aspects of RNA metabolism. They are characterised by a structurally highly conserved helicase core, composed of 2 RecA like domains connected via a flexible linker and flanked by the N and C terminus domains of the protein, as shown in figure 1.1 (Donsbach and Klostermeier, 2021). The interplay of the 9 conserved motifs of the helicase core gives these family of proteins the ability to hydrolyse ATP, bind and unwind RNA duplexes. The characteristic Motif II, also known as the Asp-Glu-Ala-Asp (D-E-A-D) motif, together with motif Q, I and VI carry out ATP binding and hydrolysis, as shown in figure 1.1 (Linder and Jankowsky, 2011).